Exposição crônica ao chumbo aumenta a reatividade vascular através de mecanismos dependentes do estresse oxidativo e da ciclooxigenase-2: ativação da via das MAPKs - Simões, Maylla Ronacher (2015)
Some studies show an association between lead exposure and the risk of cardiovascular disease. Chronic exposure to low lead concentration produces hypertension; however, the underlying mechanisms remain unclear. Thus, the aim of this study was to examine whether chronic exposure to low concentrations of lead for 30 days, affects the vascular function of aorta and mesenteric arteries, and evaluate the role of oxidative stress, the cyclooxygenase-2 dependent pathways and of MAPKs, in vascular changes induced by lead exposure. For this, aortas and mesentéric arteries were used from lead-treated Wistar rats (1st dose: 10 μg/100 g; subsequent doses: 0.125 μg/100 g, intramuscular, 30 days) and aortic vascular smooth muscle cells (VSMCs) from Sprague Dawley rats stimulated with lead (20 µg/dL) were also used. After treatment, the blood levels attained 21.7 ± 2.38 µg/dL. This exposure increased systolic blood pressure and aortic and mesenteric rings contractile response to phenylephrine, reduced acetylcholineinduced relaxation in aortic rings and did not affect sodium nitroprusside relaxation. Endothelium removal and L-NAME left-shifted the response to phenylephrine more in untreated than in aortas from lead-treated rats, however no diference was observed in mesenteric rings. When using apocynin (30 µM), we observed that there was a reduced response to phenylephrine which was greater in treated than in untreated aortas. In mesenteric rings apocynin did not change the reactivity, although SOD (150 U ml-1) led to a small reduction in vasocontriction response to phenylephrine. Indomethacin (10 μM) decreased more the response to phenylephrine in aortas and mesenteric arteries from treated than from untreated rats. The EP1 antagonist SC19220 (10 mM) reduced the response to phenylephrine only in mesenteric rings from rats exposed to the metal. Treatment with lead caused an increased vascular protein expression of gp91phox, Cu/Zn-SOD, Mn-SOD and COX-2. In cultured VSMCs lead 1) increased superoxide anion production, NADPH oxidase activity and gene and/or protein levels of NOX1, NOX4, Mn-SOD, EC-SOD and COX-2, and 2) activated ERK1/2 and p38 MAPK. Both antioxidants (mito-TEMPO-5 μmol/L, tempol-10 μmol/L e ML171-0,5 μmol/L) and COX-2 inhibitors (Celecoxib- 10 μM e Rofecoxib-10 μmol/L) normalized superoxide anion production, NADPH oxidase activity and mRNA levels of NOX1, NOX4 and COX-2. Blockade of the ERK1/2 and p38 signaling pathways abolished lead-induced NOX1, NOX4 and COX-2 expression. In conclusion, the results presented here demonstrated that treatment with low doses of lead increased systolic arterial blood pressure, promoted vascular dysfunction and activated MAPK signaling pathways. These effects are associated with the activation of inflammatory proteins such as NADPH oxidase and COX-2 that act in concert to contribute to vascular dysfunction.